2015
DOI: 10.1007/s40501-015-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Cannabis Use in Schizophrenia

Abstract: Schizophrenia I Psychosis I Cannabis use disorder I Psychosocial treatment I Pharmacological treatment Opinion statement Cannabis is used by more than 25 % of schizophrenia patients and is associated with symptom exacerbation and poorer clinical outcome. To date, evidence is scarce for treating cannabis use disorders among schizophrenia patients. Psychosocial interventions such as cognitive behavioral therapy, motivational interviewing, or contingency management have been evaluated as potential treatments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Participants reportedly utilize a range of treatments tailored to each patient, including substance abuse therapy, abstinence, and even treatment with safer cannabis compounds. Such treatment variation reflects larger uncertainty and infancy of the field, with current literature undecided on a singular accepted "best treatment" (Hjorthøj, 2009;Schultz, 2015). Furthermore, participants generally agreed that clinicians are responsible for their understanding of how to treat this patient population, leaving room for clinicians to update themselves at varied frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reportedly utilize a range of treatments tailored to each patient, including substance abuse therapy, abstinence, and even treatment with safer cannabis compounds. Such treatment variation reflects larger uncertainty and infancy of the field, with current literature undecided on a singular accepted "best treatment" (Hjorthøj, 2009;Schultz, 2015). Furthermore, participants generally agreed that clinicians are responsible for their understanding of how to treat this patient population, leaving room for clinicians to update themselves at varied frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…In simple terms, cannabis is often falsely attributed as a formidable treatment for symptoms of schizophrenia, leading patients with schizophrenia to use it erroneously. While it may afford short-term relief of symptoms of schizophrenia, the long-term result often involves psychotic relapse (Schoeler et al, 2016), worsening of symptoms, rehospitalization (Hides et al, 2006), and other products of dependence (Schultz et al, 2015), further contributing to a cycle of abuse, poor treatment outcomes, and worsened schizophrenia (Hjorthøj, 2009).…”
Section: Cannabis Use In Patients With Schizophreniamentioning
confidence: 99%
“…For instance, retrospective studies 22 , 23 and two randomized controlled trials (RCTs) 24 , 25 using atypical antipsychotics, particularly clozapine, found beneficial effects on psychosis and cannabis use. RCTs evaluating behavioral therapies (e.g., contingency management (CM), cognitive behavioral therapy) for schizophrenia and CUD, are limited as typically patients with co-occurring mental illness are excluded in CUD trials, and most studies evaluated the efficacy on cannabis use rather than CUD, or early psychosis versus schizophrenia 26 , 27 . Notably, our group demonstrated that a 28-day cannabis abstinence paradigm with CM produced high rates of abstinence (~43%) in cannabis-dependent schizophrenia outpatients, comparable to cannabis-dependent non-psychiatric controls (~55%) 28 .…”
Section: Introductionmentioning
confidence: 99%